Polaris : the chief scientist's recollections of the American North Pole expedition, 1871-73 - Bessels, Emil, 1847-1888 (Northern lights series, 2016)
"Polaris is a thoroughly edited, annotated translation of Die Amerikanische Nordpol-Expedition by Emil Bessels (Leipzig: Verlag von Wilhelm Engelmann, 1879). Bessels recounts the expedition of the ship Polaris, led by Captain Charles Francis Hall, on its failed attempt to reach the North Pole. Bessels, Polaris's chief scientist, provides a thorough account of the voyage, including detailed descriptions of St. John's, Newfoundland, Greenland settlements, Inuit people and culture, and plentiful scientific data on the flora, fauna, geography, oceans they encountered. Recent discoveries concerning a more sinister aspect of the voyage also make this a vital critical edition. While wintering at Thank God Harbour in Northwest Greenland, Hall died suddenly; Bessels proclaimed the cause of death was stroke. In 1968 English professor Chauncy Loomis and pathologist Franklin Paddock exhumed Hall's body from the permafrost, discovering that Hall had in fact been poisoned with arsenic. Bessels had the knowledge and opportunity to poison Hall, but for decades no motive could be found. However, new evidence has emerged of a romantic triangle between Hall, Bessels, and a young American sculptor Vinnie Ream, providing, at last, a motive for murder. Barr's introduction and epilogue outline the unique aspects of Bessels book, placing it in the historical context of arctic exploration. Barr has added 723 endnotes, drawing on 73 bibliographic sources, to explain and to contextualize Bessels writing. Barr's appendices cover Bessel's scientific appendix, Hall's instructions, the Board of Inquiry that followed the expedition's return, and biographies of the seven major players in this tale of exploration and murder."--